A study on the bidding strategy of the Virtual Power Plant in energy and reserve market - Huy Nguyen-Duc; Nhung Nguyen-Hong (Energy Reports, 2020)
This paper studies the bidding strategy of a Virtual Power Plant (VPP) in a market of energy and regulation service. The operation of distributed energy resources (DER) and battery energy storage inside the VPP is analyzed. A bidding strategy of the VPP including the spinning reserve contract and day-ahead offering/bidding contract is investigated. A two-stage robust optimization model is proposed to determine the VPP's purchasing/sell power in each contract to maximize the VPP's profit. The uncertainty in the DER and demand is considered in the optimization framework. The proposed model is applied to a small VPP including the photovoltaic (PV) system, battery energy storage (BESS) equipped in a customer.
Keywords: 330; Energy storage; Electricity market; Robust optimization; Spinning reserve; Virtual Power Plant